Finding and Using a Co-Packer - Alison O’Donoughue; Wendi Jennings; Soohyoun Ahn (EDIS)
A contract packager, commonly called a co-packer, is a manufacturer that will produce, package, and/or label a product for clients. This new 7-page factsheet provides a brief overview on the definition of co-packers, advantages and disadvantages of using a co-packer, and the list of things you need to consider when you hire and work with a co-packer. This factsheet is one in the Food Entrepreneurship in Florida series, which serves as a useful guide to help run a successful food-related business. Written by Alison O'Donoughue, Wendi Jennings, and Soohyoun Ahn, and published by the UF/IFAS Food Science and Human Nutrition Department.